Identifikasi dan Analisis Molekuler Hemosianin sebagai Gen Ketahanan Tubuh Udang Vaname (Litopenaeus vannamei) - Talitha Amanda; Yuni Kilawati; Maftuch (Jurnal Penelitian Pendidikan IPA, 2024)
Production of white shrimp (Litopenaeus vannamei) tends to decrease every year caused by diseases, one of which is White Feces Disease (WFD). Genetically, monitoring has been carried out on the parent characters of SPF (Specific Pathogen Free) shrimp imported from Hawaii and Florida with low genetic variation. If there is a threat such as disease caused by bacteria and the gene that codes for disease control or the body's resistance gene is missing, it allows the individual to become susceptible to disease. Gene that codes for body resistance in white shrimp is hemocyanin. Hemocyanin gene studies are needed as a first step in controlling disease in white shrimp. Method used is a descriptive method. Procedures carried out are sample collection, detection of WFD, molecular analysis of hemocyanin and data analysis. Results showed that healthy shrimp had hemocyanin while shrimp with WFD had very little or no amount of hemocyanin. Hemocyanin gene profile in healthy shrimp was also analyzed and there were 4 nucleotide change made changes to 4 amino acid. Changes in amino acids affect the stability of hemocyanin and cause polymorphism of hemocyanin. Phylogenetic analysis showed dendogram split into two clades between L. vannamei and P. monodon.